Needs Analysis of Nursing Students in English Online Learning - Wini Fitrina Sofyan; Eti Wati (Universitas Hamzanwadi, 2022)
Needs analysis is a compulsory procedure in formulating the syllabus. Since the Covid-19 has forcefully changed traditional learning into online learning, it is necessary to reanalyse students’ needs in formulating an appropriate English online learning syllabus. This quantitative study employs descriptive analysis method. The participants are 85 sophomore students of nursing bachelor program at STIKes YPIB Majalengka. This study aims to describe the needs of students that are categorized into six aspects with the following results: 1) the students’ current situation, shows that the students need more support to facilitate internet networks and online learning devices (n=52,61%). 2) The skills and prior knowledge, this shows that numerous students tremendously need to develop their vocabulary, structures and the four basic skills (n=66,76%). 3) The learning difficulties, it describes that many students need assistance in finding their online learning styles (n=44,52%). 4) The motivation, many students need strong initiation to find their online learning motives (n=53,62%). 5) The perception, they need strong encouragements to increase their self-esteem in an online classroom setting (n=51,60%). The last, 6) the expectation, almost all students need online learning methods that more varied and interesting (n=83,98%).